The Role of Generative Adversarial Networks in Transforming Creative Industries: Innovations and Implications - Narendra Sharad Fadnavis (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research report mainly emphasizes the transformational impacts of the Generative Adversarial Networks (GANs) technology that are related to the creative industries, including the music, art, fashion, and other filmmaking industries. It mainly leverages deep learning technology and mimics human creativity pushing the boundary of the creativity fields. It contains different highlights that enhance the social and economic implications through model training methods that address the authorship, and copyright and also preserve traditional human creativity. Thus it concludes the enhancement of the GAN architecture and includes the development of the ethical frameworks that foster interdisciplinary collaboration through AI integration.